2013
DOI: 10.1021/cm4027682
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Salt Flux Growth of LiFePO4 Single Crystals with Controlled Defect Concentrations

Abstract: Improved methods for the flux growth of single crystals of the important battery material LiFePO 4 have been developed, allowing the facile preparation of single crystals up to 1 cm across with well-developed facets at relatively low temperatures. The structural characterization of these samples by both powder X-ray diffraction and single crystal diffraction (X-ray and neutron) indicates that the samples are typically stoichiometric with a very low concentration of Fe defects on the Li site, though crystals wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 26 publications
2
42
0
Order By: Relevance
“…Needle-shaped APT specimens of LFP were fabricated by focused ion beam liftout and were mounted onto commercial silicon flat-top micro-post arrays [20]. The LFP liftouts were extracted from a single crystal grown by a flux growth method reported elsewhere [21]. All specimens were analyzed in the [100] crystal orientation, although no crystallographic features were apparent in the subsequent APT reconstructions.…”
Section: Methodsmentioning
confidence: 99%
“…Needle-shaped APT specimens of LFP were fabricated by focused ion beam liftout and were mounted onto commercial silicon flat-top micro-post arrays [20]. The LFP liftouts were extracted from a single crystal grown by a flux growth method reported elsewhere [21]. All specimens were analyzed in the [100] crystal orientation, although no crystallographic features were apparent in the subsequent APT reconstructions.…”
Section: Methodsmentioning
confidence: 99%
“…9,10 With the aid of this technique, Chung et al 33 discovered the localized aggregation behavior of Fe Li . 34 On the basis of their observations, a vacancy-driven mechanism was proposed for the formation of the localized defect segregation (Figure 3a). 35 In addition to unraveling the defect distribution, electron microscopy has also been used for the detailed investigation of the intercalation mechanisms in LFP.…”
Section: Electrode Materialsmentioning
confidence: 99%
“…Shao‐Horn et al indirectly observed lithium and oxygen in LiCoO 2 cathode through exit wave reconstruction from focal series of high resolution TEM images, but this method is operationally complicated and computationally expensive, and cannot be routinely applied to characterize a wide range of electrode materials. High‐angle annular dark‐field (HAADF) imaging based on aberration‐corrected STEM has enabled direct imaging of the atomic structure of electrode materials, for example, the antisite defect (i.e., Fe ions on Li sites) in LiFePO 4 that has been demonstrated to impede lithium diffusion . However, the contrast in HAADF image is proportional to Z 1.7 ( Z refers to atomic number) .…”
Section: Introductionmentioning
confidence: 99%